2021
DOI: 10.1101/2021.07.21.453238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dichloroacetate improves systemic energy balance and feeding behavior during sepsis

Abstract: Sepsis is a life-threatening organ dysfunction by dysregulated host response to an infection. The metabolic aberrations associated with sepsis underly an acute and organism wide hyper-inflammatory response and multiple organ dysfunction; however, crosstalk between systemic metabolomic alterations and metabolic reprograming at organ levels remains unknown. We analyzed substrate utilization by the respiratory exchange ratio, energy expenditure, metabolomic screening and transcriptional profiling in a cecal ligat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Previous studies of murine sepsis demonstrate that in vivo targeting of PDHK with DCA, administered as a single dose of 25 mg/kg 24 h post CLP, increases the septic survival rate to 71%, whereas the CLP animals not receiving DCA treatment had a survival rate of only 10% over the 14-day observation period (McCall et al, 2018). Despite the less effect of PDHK inhibition on LPS-induced cytokine expression in BMDMs ( Figures S1H-S1I ), very recently, our group demonstrated that in vivo PDHK inhibition by DCA lowered plasma non-inflammasome cytokines, including TNF and IL-6 in the CLP mice (Oh et al, 2022), suggesting an anti-inflammatory effect of PDHK inhibitors in bacteria-infected animals. Given that macrophage NLRP3 inflammasome plays a critical role in the pathogenesis of sepsis, we asked whether DCA confers survival partially through down-regulation of the NLRP3 inflammasome during sepsis.…”
Section: Resultsmentioning
confidence: 86%
“…Previous studies of murine sepsis demonstrate that in vivo targeting of PDHK with DCA, administered as a single dose of 25 mg/kg 24 h post CLP, increases the septic survival rate to 71%, whereas the CLP animals not receiving DCA treatment had a survival rate of only 10% over the 14-day observation period (McCall et al, 2018). Despite the less effect of PDHK inhibition on LPS-induced cytokine expression in BMDMs ( Figures S1H-S1I ), very recently, our group demonstrated that in vivo PDHK inhibition by DCA lowered plasma non-inflammasome cytokines, including TNF and IL-6 in the CLP mice (Oh et al, 2022), suggesting an anti-inflammatory effect of PDHK inhibitors in bacteria-infected animals. Given that macrophage NLRP3 inflammasome plays a critical role in the pathogenesis of sepsis, we asked whether DCA confers survival partially through down-regulation of the NLRP3 inflammasome during sepsis.…”
Section: Resultsmentioning
confidence: 86%